1999
DOI: 10.1046/j.1523-1755.1999.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of calcium oxalate crystals by albumin: Involvement in the prevention of stone formation

Abstract: Promotion by albumin of calcium oxalate crystallization with specific formation of the dihydrate form might be protective, because with rapid nucleation of small crystals, the saturation levels fall; thus, larger crystal formation and aggregation with subsequent stone formation may be prevented. We believe that albumin may be an important factor of urine stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
59
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 55 publications
(7 reference statements)
2
59
1
Order By: Relevance
“…It has been reported that the occurrence of COM, the more thermodynamically stable polymorph of calcium oxalate, is often at the core of most kidney stones and is approximately twice as frequent as COD (2), although both crystal types typically exist to some degree in most stones (3,4). COM is commonly found in the urine of "stone formers," but seldom is seen in healthy urine; on the other hand, COD crystals are typically found in the urine of both healthy people and stone formers and are routinely excreted during urination (5)(6)(7). Importantly, in patients with severe uremia and hypercalciuria, elongated, large rod-shaped COD crystals are not only often observed but are the sole mineral phase present in the kidneys in these pathologies (8,9).…”
mentioning
confidence: 99%
“…It has been reported that the occurrence of COM, the more thermodynamically stable polymorph of calcium oxalate, is often at the core of most kidney stones and is approximately twice as frequent as COD (2), although both crystal types typically exist to some degree in most stones (3,4). COM is commonly found in the urine of "stone formers," but seldom is seen in healthy urine; on the other hand, COD crystals are typically found in the urine of both healthy people and stone formers and are routinely excreted during urination (5)(6)(7). Importantly, in patients with severe uremia and hypercalciuria, elongated, large rod-shaped COD crystals are not only often observed but are the sole mineral phase present in the kidneys in these pathologies (8,9).…”
mentioning
confidence: 99%
“…Albumin preferentially leads to the formation of COD (CaOx dehydrate) crystals over COM (CaOx monohydrate), a similarly favorable formation of COD has also been reported with the use of (BSA), a homolog of HSA [26,27]. These crystals are small and are easily removed in comparison to their larger counterparts (COM crystals).…”
Section: Hsa In Urolithiasismentioning
confidence: 63%
“…Furthermore, quite contradictory to its nature as a promoter of nucleation in CaOx crystals, albumin inhibits aggregation in a concentration-dependent manner. Although, this involvement in the nucleation process might just be benign [26].…”
Section: Hsa In Urolithiasismentioning
confidence: 99%
See 2 more Smart Citations